PRESERVICE TEACHERS’ BELIEFS AND PRACTICES IN TEACHING ENGLISH TO YOUNG LEARNERS - Othman, Juliana; Kiely, Richard (Universitas Pendidikan Indonesia, 2016)
This paper explores ESL preservice teachers’ beliefs regarding teaching English to young learners, and examines the interplay between their beliefs and instructional practices. Seventy ESL preservice teachers at a university in Malaysia participated in the study. Data is drawn from semi-structured interviews and lesson plan analysis. The results indicated that the preservice teachers’ classroom practices did not often reflect their stated beliefs about young learners language learning. Although there was a strong consensus that English should be taught communicatively, the preservice teachers also employed structural based approach when teaching grammar. Contextual factors hindering this consistency were attributed to exam focused instruction and time constraints. Thus, this paper argues that reform in language teacher education need to address factors that hinder preservice teachers from implementing instructions which aligns with the theoretical beliefs espoused by their teacher training program.